Skill Acquisition and Korean Landscape Architecture: An Ethnographic Account of Skateboarding in Seoul, South Korea. (October 2019) - Holsgens, Sander
This article sketches a phenomenology of South Korean skateboarding. Drawing on more than 6 years of experience in the region and 20 months of fieldwork, I explore how Seoul-based skaters negotiate their presence in the built environment through precise spatial expertise, minute bodily gestures, and everyday skillful learning. Specifically, I think through the ways in which architectural minutiae within skate parks affect the skaters' perceptual experience of the built environment. Significantly, the architectural typology of the Korean skate parks is experienced as spaces of stillness, closeness, and tranquility, providing a serene and placid alternative to the interpretation of skateboarding as a fundamentally spectacular and trick-driven practice.